PROCEDURE FOR TAXATION OF INCOME OF SELF-EMPLOYED PERSONS - Nodira Ashuraliyevna SAFAROVA (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article analyzes the scientific-theoretical views on self-employment, its role in ensuring the employment of the population, and the activities of self-employed persons by industry. Also, the procedure for taxing the income of self-employed persons is explained.